INTELIGENCIA ARTIFICIAL EN RADIOLOGÍA DENTAL: ENTRE LAINNOVACIÓN TECNOLÓGICA Y LA RESPONSABILIDAD CLÍNICA - Dias da Silveira, Heraldo Luís (2026)
The integration of artificial intelligence (AI) within oral radiology signifies a fundamental shift in the interpretation of images and their subsequent application in clinical judgment. Algorithms leveraging deep learning have shown reliable efficacy in identifying caries, periapical lesions, root resorptions, and periodontal bone changes, frequently achieving sensitivity and specificity metrics that are either on par with, or in some instances, exceed those of human practitioners. The rapid dissemination of these technologies demands a critical analysis that transcends mere performance validation. Radiological practice is not limited to identifying patterns in images, but involves clinical contextualization and the integration of multiple variables, which still represents a limitation of automated systems. In this sense, the risk of uncritical automation of diagnosis cannot be neglected.